Determination of Pesticide Residues in Sediment, Water and Fish from Some Selected Agricultural Sites in Bauchi State, Nigeria - Kolo, Babagana; Aminu Mohammed, Umar; Aliyu Shehu, Aísha; Hassan Jibrin, Halima (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
ABSTRACT Pesticide residues play a crucial role in the health of human through bio-accumulation through food chain or food web. The study was conducted to determine the pesticide residues (abamectin, aldrin, chlorpyrifos, cyhalotrin, cypermethrin, dichlorvos, glyphosate, heptachlor, Imadachlorpid) present in sediment, fish and river water samples from some agricultural sites in Bauchi state. Samples were extracted and analyzed by High Performance Liquid Chromatography (HPLC). Fish samples were analyzed based on organs (gills, flesh, liver, and kidney) with a pesticide residue value ranged from 0.06±0.08ppm to 0.16±0.24ppm in Gadau site, 0.04±0.01ppm to 2.5±3.37ppm in Giade site and 0.04±0.00ppm to 0.06±0.03ppm in Jama’are site. The sediment samples 0.09±0.00ppm to 13.70±13.46ppm, 0.97±0.00ppm to 24.15±31.28ppm and 0.04±0.00ppm to 6.93±13.38ppm at Gadau, Giade and Jama’are sites respectively. Meanwhile the river water sample had a ranged value of pesticide residues as 0.15±0.15ppm to 1.04±1.50ppm, 0.11±0.00ppm to 3.34±4.29ppm and 0.17±0.16ppm to 8.20±7.38ppm from Gadau, Giade and Jama’are sites. Jama’are samples were less contaminated with the organophosphorus pesticide residues and the other corresponding sampling sites. Dichlorvos and Heptachlor were found to be higher than the permissible limits of 0.1 mg/kg and 0.01mg/kg in all the samples that were determined except where not detected. Also farmers should be educated on a proper usage of the pesticides they use and the implications of using too much of it to the environment..